Generalized integral type mappings on orthogonal metric spaces - Ö. Acar; E. Erdoğan; A.S. Özkapu (Karpatsʹkì Matematičnì Publìkacìï, 2022)
This study is devoted to investigate the problem whether the existence and uniqueness of integral type contraction mappings on orthogonal metric spaces. At the end, we give an example to illustrative our main result.